Evolution or Entropy of the Concept of Chilling Effect? – Polish Perspective - Kos, Katarzyna (Teisė, 2019)
[full article, abstract in English; abstract in Lithuanian] The concept of chilling effect, formulated in the beginning of the second half of the 20th century by the Supreme Court of the United States of America, has been applicated both in common law and in continental law system. Lately, also the Polish Constitutional Tribunal more often has used it. Despite the U.S. Supreme Court bound the chilling effect with infringement of the freedom of speech, nowadays it seems to be useful to describe also interferences to other human rights. The European Court of Human Rights has developed that kind of interpretation. It has occurred that the notion of chilling effect perfectly describes any interference into right or freedom consisting of deterring of a person from undertaking by he or she an action. The Polish Constitutional Tribunal has drawn the concept of the chilling effect directly from adjudication of the ECHR. But without broad justification it also applicates this notion to constitutional issues connected with provisions concerning the system of government. This process of adaptation of the chilling effect concept provokes questions whether this notion was properly rooted in the Polish constitutional system. The Polish Constitutional Tribunal has not deeply explained how to understand the concept of chilling effect and in what occurrences it may be applied. Without clear statement of the Polish Constitutional Tribunal we can say that the chilling effect concept may not be applied only in the cases concerning rights and freedoms which imply act of deterrence, like prohibition of compelling to participate or not participate in religious practices. Moreover, we can only assume that identifying the chilling effect does not overjudge the result of constitutional review, it is just an argument for unconstitutionality.